Characterization of a proteolytically stable d-Peptide that suppresses herpes simplex virus 1 infection implications for the development of entry-based antiviral therapy - Jaishankar Dinesh (JOURNAL OF VIROLOGY, 2015)
Uncontrolled herpes simplex virus 1 (HSV-1) infection can advance to serious conditions, including corneal blindness or fatal encephalitis. Here, we describe a highly potent anti-HSV-1 peptide (DG2) that inhibits HSV-1 entry into host cells and blocks all aspects of infection. Importantly, DG2 is highly resistant to proteases and shows minimal toxicity, paving the way for prophylactic or therapeutic application of the peptide in vivo.